Bilateral Transposition Flap for Postoperative Anal Stenosis after Reconstruction for Paget Disease - Kengo Nakatsuka, MD; Ryo Karakawa, MD; Yuma Fuse, MD; Hidehiko Yoshimatsu, MD; Tomoyuki Yano, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. One of the complications of anal surgery or disease is anal stenosis. To release the tension of the anus, a tension-releasing incision in the perianal skin and various anoplasty procedures are usually considered. The aim of this article is to describe a straightforward technique with local flaps for severe anal stenosis after anal reconstruction. A 57-year-old man presented to the clinic with diverticulitis secondary to severe anal stenosis, and reported difficulty with defecation after perianal skin resection around the anus and surgery to create a V-Y advancement flap for perianal primary Paget disease 9 months previously. After improvement of the diverticulitis using antibiotics, bilateral transposition flaps were transferred to release the anal stenosis. The surgical treatment for severe anal stenosis has been known to entail several complications, including infection, incontinence, anal mucosal ectropion, pruritus, wound dehiscence, and restenosis. In this severe case, because the scars were situated at the 6 o’clock and 12 o’clock positions on the anus due to the previous V-Y advancement flap, bilateral rotation flaps were transferred from the 3 o’clock and 9 o’clock positions of the anus to prevent wound dehiscence and partial flap necrosis. Three months later, the size of the anus was unchanged, but additional surgery was performed at the patient’s request. A bilateral transposition flap procedure was used, with flaps designed and elevated from the 6 o’clock and 12 o’clock positions. The postoperative course was uneventful, and the anal stenosis was improved.